Wild fauna with use value in the Biosphere Reserve Sierra de Huautla, Morelos, Mexico - Valle Marquina, Raúl (2021)
The aims of this paper were the systematization of appropriated species, appropriation forms and assigned use values of wildlife species in the Biosphere Reserve of the Sierra de Huautla, Mexico, by means of documentary analysis and field work. We recorded 46 species with use value pertaining to 31 families. Birds accounted for the highest number of appropriated species (42.5%), followed by mammals (34%). Of the total species, 64% are appropriated for alimentary purposes and are used in the treatment of diseases in traditional medicine. Others are used as ornaments, talismans, in tool manufacture and as pet animals. Wildlife appropriation is achieved by hunting, collection and fishing. Fire arms such as shotguns are the main instrument used in hunting. Dogs, machetes, slingshots, nets, hooks, slipknots, are also used, or they are captured by hand. Appropriation can be an opportunistic or organized activity by means of “arreadas” (herding), “espiadas” (opportunistic observation), “lampareadas” (spotlighting), “campeadas” (scouring), “acorralamiento” (cornering) and manual collection. Wildlife appropriation is a culturally rooted activity in the reserve communities. Nevertheless, the analysis of the relationship society-fauna in the region is limited and this is why the generation of information that may enable a sustainable management of the faunistic resource is necessary.